Relación entre la calidad de servicio y la fidelización de clientes en las estaciones de servicio de combustible en Chimbote, Perú - Lavalle Noriega, Oscar Enrique (2022)
This research was performed at a Gasoline Service Station located in Chimbote. In particular, customer loyalty to the quality of the service provided has been studied, because a fundamental aspect of the success of a company is to get a loyal customer, who repeats his visit to the station assiduously, recommends the service to others and can tolerate an occasional failure, but without deserting, all thanks to the relationship generated over time. The research methodology has an explanatory scope, a non-experimental design with a quantitative approach being the independent variable of study, quality of service and the dependent variable customer loyalty. A questionnaire was used as an instrument using the SERVPERF methodology, employing the Likert scale to evaluate the level of customer loyalty. This was applied to a sample of 122 customers, with the result that the company provides quality service; however, it should improve the application of loyalty programs in accordance with the type of customer it has. The conclusion can be drawn that service quality is significantly associated with customer loyalty at the service station in the city of Chimbote – Perú.